Understanding the arrangement of Eucalyptus-Marandu palisade grass silvopastoral systems in Brazil. (February 2022) - Vieira Junior, Nilson Aparecido; Evers, Jochem; dos Santos Vianna, Murilo; Pedreira, Bruno Carneiro e; Pezzopane, José Ricardo Macedo; Marin, Fábio Ricardo
Abstract: CONTEXT: Limited land availability and an increasing global population are challenges faced by the agricultural sector in the coming decades. The silvopastoral system is an efficient alternative to full sun pastures that could be used to sustainably intensify animal and crop production. However, the adoption of this system is being held back by a lack of knowledge on how the trees in such a system should be arranged in order to avoid detrimental effects on pasture growth. OBJECTIVE: The aim of this study was to test different arrangements of trees in the Eucalyptus -Marandu palisade grass silvopastoral system and to evaluate its performance in different regions of Brazil. METHODS: A functional-structural plant model was developed to simulate radiation interception by trees and was then coupled to the CROPGRO-Perennial Forage model to simulate the production of forage biomass. Considering solar radiation as the main resource under competition, water interactions that occur under-ground between Eucalyptus and Maranu palisade grass were not considered. The models were calibrated with experimental data collected in silvopastoral systems in Brazil. The silvopastoral systems were selected according to a combination of tree row spacing (15, 30, and 45 m), two row orientations (north-south and east-west), and single or triple rows. Simulations were replicated for different tree ages (2, 4, 6, 8, 10 and 12 years) representing different levels of shading. RESULTS AND CONCLUSIONS: Our simulations show that the tree arrangement has a significant effect on the incidence of radiation on the pasture, resulting in different levels of forage production. Row spacing of 30 and 45 m is suitable for providing forage for the animals for several years. In contrast, tree arrangements with a row spacing of 15 m or triple lines demand more careful planning and management, taking into account the soil and climatic characteristics of each region. Lower declines in the forage production were observed in arrangements of 45 m, varying from 1000 and 3000 kg ha −1 after 6 years of system establishment. In this period, the annual production level was lower than 14, 000 kg ha −1 for arrangments with row spacing of 15 and 30 m, being recommend pruning and thinning practices aiming to increase the radiation incidence within the system. SIGNIFICANCE: The approach used in this study can be extended to other combinations of species and environments to aid the planning and management of this kind of system. Graphical abstract: Unlabelled Image Highlights: Silvopastoral systems may improve the sustainability of livestock by integrating trees, pastures, and animal production. Silvopastoral systems adoption is held back by a lack of knowledge about the arrangement of trees. We simulated and evaluated different arrangements of trees in silvopastoral systems in Brazil. A high level of shading for tree arrangements with a row spacing of 15 m demands more careful planning and management. This study may aid the planning and management of this kind of system combining other species and environments.